Stress analysis of radial and non- radial nozzle connections in ellipsoidal head pressure vessel / Haszeme Abu Kasim and Professor Dr. Ir. - Professor Dr. Ir., Haszeme Abu Kasim (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2013)
One of the critical aspects in designing pressure vessels is the nozzle connections in the ellipsoidal head of two intersecting shells. This paper presents a parametric study using Finite Element Analysis (FEA) method to determine the influence of the non-geometric parameters for a radial and non-radial nozzle connections in ellipsoidal heads vessel subjected to internal pressure and various external loadings. All the results analysis for both radial and non-radial nozzle for each load case applied, presented as graphs of non-dimensional parameters against stress concentration factor (SCF). In order to validate the FEA method, an analytical investigation of thin shell theory used for radial nozzle subjected to internal pressure loading. The comparison results between both methods show that the FEA method was reliable and valid in this research with only less than 10% differences.